SIFAT FISIK TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA OLOBOJUKABUPATEN SIGI - Delsiyanti, DanangWidjajanto, Ulfiyah A. Rajamuddin, Delsiyanti (AGROTEKBIS, 2016)
This research aim is to know the characteristics of soil physic on some land use system in oloboju village sigi district of Sigi Biromaru. The research has done on the Sigi 6 units of rice field, the dry field and mixed farm with the slope of 0-8% and 8-15%. Soil analysis has in soil science Laboratory, Faculty Of Agriculture, University Tadulako. The research was done on March until May 2016. Determination of soil sample Location taken for analyse laboratory determined in the Purposive Sampling so that it sets 18 sample poin. Soil sample was taken as much as 3 replications for every land use. The result of research showed that soil physical from oloboju on 6 unit land with different land slope have different soil physical, soil characteristics dominated by texture the faction of dust and sand, with the soil texture are silt loam, moderate organic matter, moderate bad, permeability, porosity, field capacity and saturated water were low until high, liquid limitation and plasticity were moderate until high. The characteristic of the soil on 6 land units, in general, determined by texture and organic matter.